Nilai Edukasi dan Spiritualitas dalam Tradisi Tedak Siten di Desa Bancar dalam Perspektif Islam Nusantara - Muhammad Shohibul Ma’ali; Nisa Uzzaroh; Intan Dzihriyati; Nurul Hakim (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Indonesia is a country rich in cultural diversity, one of which is the Tedak Siten tradition that is still preserved by Javanese communities, including those in Bancar Village. This tradition is not merely a cultural heritage but also contains important educational and spiritual values in community life. This study aims to understand the meaning of the Tedak Siten tradition, identify the educational and spiritual values embedded within it, and analyze it from the perspective of Islam Nusantara. The research employs a qualitative descriptive approach using observation, interviews, and documentation techniques, with informants selected purposively from community members directly involved in the tradition. The findings reveal that Tedak Siten functions as a medium for character education, instilling values such as independence, responsibility, and perseverance from an early age. In addition, the tradition strengthens spiritual values through prayers and expressions of gratitude to Allah SWT. From the perspective of Islam Nusantara, Tedak Siten reflects a harmonious acculturation between local culture and Islamic teachings without contradicting the principle of monotheism. The implications of this study indicate that local traditions can be utilized as contextual learning resources in Islamic education while also serving as a means of preserving valuable cultural heritage. Therefore, Tedak Siten remains relevant not only as a tradition but also as a medium for character building and strengthening religious values in society.